The Relationship of Physical Activity with Premenstrual Syndrome in Students of the Faculty of Health Nahdlatul Ulama Surabaya University - Fisqiyatut Thaharah Fisqi; Wiwik Afridah (Journal of Health Community Service, 2025)
Premenstrual Syndrome is a common health problem that most women of reproductive age complain about. There are more female students of the Faculty of Health than boys and all female students are of productive age. This study aims to analyze the relationship between physical activity and the incidence of PMS in students of the Faculty of Health, Nahdlatul Ulama University, Surabaya. The method in this study is correlational analytic which examines the relationship between variables with a cross sectional study approach. The sample in this study were students of the Faculty of Health, Nahdlatul Ulama University, Surabaya, which consisted of 4 study programs with a total of 39 samples. The sampling technique was stratified random sampling with the criteria of active students from the Faculty of Health, Nahdlatul Ulama University, Surabaya, aged 18-27 years and had menstruated. Analysis of the research data using the Spearman Rank Test. The results of the physical activity research of 39 respondents, had a light category as many as 22 (56.4%), a moderate category as many as 15 (38.5%), and a heavy category as many as 2 (5.1%). The results of the research that have been carried out show as many as 16 (41.0%) respondents do not experience PMS, and as many as 23 (59.0%) respondents experience PMS. The results of the bivariate analysis are known to be Sig. (2-tailed) of 0.000 is smaller than 0.1, meaning that there is a significant relationship between physical activity and the incidence of PMS. The correlation coefficient is 0.938, meaning that the level of strength of the relationship between physical activity and the incidence of PMS is very strong. The conclusion of this study is that there is a relationship between physical activity and the incidence of PMS with a strong relationship level. It is expected that female students can carry out regular physical activity by exercising for 30 minutes for 4-6 times a week, or walking one hour per day, in order to improve health and reduce the impact of PMS.